Recent development in the strategies projected for chikungunya vaccine in humans - Goyal M; Chauhan A; Goyal V; Jaiswal N; Singh S; Singh M (Dove Medical Press, 2018)
Manu Goyal,1 Anil Chauhan,2 Vishavdeep Goyal,3 Nishant Jaiswal,1,2 Shreya Singh,4 Meenu Singh1,2 1Department of Pediatrics, Postgraduate Institute of Medical Education and Research, Chandigarh, India; 2Indian Council of Medical Research Advanced Centre for Evidence Based Child Health, Postgraduate Institute of Medical Education and Research, Chandigarh, India; 3Apollo Hospitals International Limited, Ahmedabad, India; 4Department of Medical Microbiology, Postgraduate Institute of Medical Education and Research, Chandigarh, India Abstract: The unprecedented epidemic spread of chikungunya worldwide illustrates the critical need for potent vaccines and therapeutic interventions. The morbidity and mortality associated with this arboviral infection has become a major public health problem in many countries across different continents. Increasing public–private partnerships have opened new avenues in research and development of vaccines. This review mainly focuses on the recent advances in patented approaches for chikungunya vaccine development and the forthcoming challenges. Keywords: chikungunya, epidemics, CHIKV vaccine candidates, clinical trials, humans